1065 Consultant led Specialist paediatric palliative care team provision in the UK: the ENHANCE Study on end-of-life care for children. (17th August 2022) - Bedendo, Andre; Papworth, Andrew; Hackett, Julia; Haynes, Andrew; Weatherly, Helen; Hinde, Sebastian; Walker, Gabriella; Murtagh, Fliss; Beresford, Bryony; Fraser, Lorna
Abstract : Aims: Although there are increasing numbers of paediatric palliative care services in the UK, they vary in their professional configuration, services provided, funding sources and population served. There is little evidence on the quality of care provided, and the outcomes of children and their families who use these services. Most of the recommendations in the NICE guidance for end-of-life care for children are based on low quality evidence. The ENHANCE study aims to identify and investigate what components of end-of-life care for infants, children and young people can have an impact on outcomes and experiences for children and their families. As part of this work, we conducted a survey of consultant led Specialist Paediatric Palliative Care Teams (SPPC) across the UK. Methods: All consultant-led SPPC in the UK were identified via the Association of Paediatric Palliative Medicine and invited to participate in an online-based survey via Qualtrics. Data were collected from September to November 2021. Questions included the type of care provided, number of referrals in 2019 (or equivalent reporting period), members of the SPPC team (as per NICE recommendations), and the extent of third-sector funding. Results: We had a 100% response rate: Seventeen clinical leads from hospital- or hospice-based SPPC teams responded to the survey. The median number of referrals to the services in 2019 was 131 (Q1-Q3: 77, 166). Only 35% (N=6) services met NICE guidance on minimum requirement for a SPPC team. All services had doctors and 82% (N=14) nurses specialist trained in palliative care as part of the core team. Among other members, chaplain/spiritual care staff was the most frequently reported (N=10, 59%), followed by family support workers (N=8, 47%) and pharmacists (N=7, 41%). Thirty-five percent of the teams had a psychologist or social worker. Only two (12%) services reported having dedicated bereavement support staff. All services reported providing symptom management, specialist nursing care, end-of-life planning and care, and supporting discharges and transfers to home or hospice for the child's final days/hours. Most services also provide care coordination (82.4%), bereavement support (76.5%), psychological care (58.8%), and social work/welfare support (52.9%). All teams received referrals from neonatal and paediatric intensive care services, and only one did not receive referrals from maternity. Most of the services also receive referrals from children and teenage, and young adult cancer services (88% and 82%, respectively). In 2019, the main source of referral was paediatric intensive care (Median 19, Q1-Q3: 8, 31), followed by neonatal intensive care (Median 10, Q1-Q3: 5, 14), and children's cancer services (Median 10, Q1-Q3: 7, 15). Forty-seven percent of the teams had at least one or more posts fully funded, and 76.5% had one or more posts funded partially or fully by a charity. Conclusion: In conjunction with previous studies, this survey has shown an increasing number of consultant-led SPPC services exist in the UK. However, a third still do not have all the professionals recommend by the NICE guidance and three-quarters are relying on posts funded by charities rather than the NHS. Funding: NIHR (Ref: NIHR129213)